2021
DOI: 10.1177/23337214211020164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Health and Well-being of Informal Caregivers of People with Dementia: A Rapid Systematic Review

Abstract: Background: In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or COVID-19, raised worldwide concern. Since then, the COVID-19 pandemic has negatively influenced health and wellness across the globe and caused nearly three million deaths. This study focuses on informal caregivers of people with dementia, a disease that affects about 50 million older adults worldwide and requires much caregiving support. Objective: Examine the current literature on the impact of COVID-19 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 29 publications
4
43
0
1
Order By: Relevance
“…In fact, the action of caregiving and taking care of a family member can be considered as a stressor that might impact GWB (Thomas et al, 2017); this aligns with the results of another study that indicated that caregivers manifested a lower mental health and reported a lower level of wellbeing compared to non-caregivers (Berglund et al, 2015). More specifically, during the COVID-19 pandemic, an impact was shown on the GWB of caregivers, which caused significantly higher levels of anxiety and depression than before the pandemic (Hughes et al, 2021).…”
Section: Fear Of Covid-19supporting
confidence: 78%
“…In fact, the action of caregiving and taking care of a family member can be considered as a stressor that might impact GWB (Thomas et al, 2017); this aligns with the results of another study that indicated that caregivers manifested a lower mental health and reported a lower level of wellbeing compared to non-caregivers (Berglund et al, 2015). More specifically, during the COVID-19 pandemic, an impact was shown on the GWB of caregivers, which caused significantly higher levels of anxiety and depression than before the pandemic (Hughes et al, 2021).…”
Section: Fear Of Covid-19supporting
confidence: 78%
“…Already a few years ago, researchers identified informal carers of people with dementia as the invisible second patients [ 27 ] who experience a high level of burden, organizational strain, psychological and physical morbidity and social isolation [ 27 , 28 ]. In the face of an ongoing pandemic, previously recognized issues seem to be escalated [ 25 ]. The frequently high levels of stress associated with caring for a person living with dementia [ 28 ] have been intensified even further by the pandemic and have negatively influenced carers’ overall psychological well-being [ 8 , 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that constraints in social participation of a person with dementia and limited access to social services have affected the entire family system, particularly the primary informal carer [22,23], who is usually left alone with their caring responsibilities due to the reduction in all forms of support they previously obtained [24]. Research conducted since the outbreak of the COVID-19 pandemic [25] appears to reinforce the finding from pre-pandemic research on informal carers' burden [26]. Already a few years ago, researchers identified informal carers of people with dementia as the invisible second patients [27] who experience a high level of burden, organizational strain, psychological and physical morbidity and social isolation [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This SARS-CoV-2 pandemic, and the lockdown associated with it in several countries (e.g., Spain), besides having a negative impact on the psychological well-being of ICs [24][25][26], has exposed the shortcomings that exist in healthcare structures such as Alzheimer associations and day care and residential centers, revealing that these are insufficient for tackling a situation that requires providing greater protection to the most vulnerable elderly [27]. In line with the third goal of the UN's Agenda 2030 for Sustainable Development "Ensure healthy lives and promote wellbeing for all at all ages" [28], we need to develop strategies to adapt and strengthen social and healthcare for the vulnerable elderly population such as people with dementia (PwD) and their ICs.…”
Section: Introductionmentioning
confidence: 99%